Local Economic Structure and Growth - Almeida, Rita (World Bank, Washington, DC, 2012)
The author tests how the local economic structure-measured by a region's sector specialization, competition, and diversity-affects the technological growth of manufacturing sectors. Most of the empirical literature on this topic assumes that in the long run more productive regions will attract more workers and use employment growth as a measure of local productivity growth. However, this approach is based on strong assumptions about national labor markets. The author shows that when these assumptions are relaxed, regional adjusted wage growth is a better measure of regional productivity growth than employment growth. She compares the two measures using data for Portugal between 1985 and 1994. With the regional adjusted wage growth, the author finds evidence of Marshall-Arrow-Romer (MAR) externalities in some sectors and no evidence of Jacobs or Porter externalities in most of the manufacturing sectors. These results are at odds with her findings for employment-based regressions, which show that concentration and region size have a negative and significant effect in most of the manufacturing sectors. These employment-based results are in line with most of the existing literature, which suggests that using employment growth to proxy for productivity growth leads to misleading results.